A dual-site FeN6-CoN4 electrocatalyst and its preparation method and application

By preparing the two-site FeN6-CoN4 electrocatalyst, the problems of reduced activity and poor stability of the existing ORR catalysts are solved, and efficient oxygen reduction reaction and good stability are achieved, which is better than traditional precious metal Pt-based catalysts.

CN118925771BActive Publication Date: 2025-02-18PINGDINGSHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410978453.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-22
Publication Date
2025-02-18
Estimated Expiration
2044-07-22

AI Technical Summary

Technical Problem

The existing ORR catalysts have problems of reduced activity and poor stability in oxygen reduction reactions, especially due to the unsaturation characteristics of Fe-Nx sites, which intensifies the Fenton reaction and precipitates the active site, reducing the ORR activity and stability of the catalyst. .

Method used

Using a two-site FeN6-CoN4 electrocatalyst, the carbon nitride C3N4 is synthesized as a support, and it is uniformly dispersed and adsorbed in situ with Co salt and Fe salt to form a Fe-Co-N precursor complex. After multiple steps, it is treated as Vacuum drying, annealing and etching to prepare FeN6-CoN4 catalyst with the highest Fe coordination.

Benefits of technology

It improves the catalytic activity of oxygen reduction, reduces the generation of H2O2, enhances the stability of the Fe site, inhibits Fe precipitation, and significantly improves the ORR activity and stability of the catalyst, which is better than traditional precious metal Pt-based catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118925771B_ABST
    Figure CN118925771B_ABST
Patent Text Reader

Abstract

The present invention discloses a dual-site FeN6-CoN4 electrocatalyst and its preparation method and application, comprising the following steps: the first step: synthesizing carbon nitride C3N4; the second step: taking the C3N4 carrier and ultrasonically dispersing it uniformly in deionized water and stirring, dripping pyrrole monomer, keeping for 18-24h, using electrostatic interaction to adsorb monomers, adding Co salt and Fe salt in proportion, stirring continuously, filtering, vacuum drying, annealing and heat preservation in a tubular furnace nitrogen atmosphere and cooling to room temperature, etching with H2SO4 solution, centrifugal washing to neutrality, vacuum drying, and obtaining the target catalyst FeN6-CoN4. In the FeN6-CoN4 dual-site electrocatalyst of the present invention, the CoN4 site not only serves as an oxygen reduction active site, but also the dual-site synergistic effect improves the oxygen reduction catalytic activity, promotes the oxygen adsorption cracking mechanism, reduces the joint mechanism, reduces H2O2, and at the same time, the saturated coordination structure FeN6 enhances the stability of the Fe site, inhibits Fe precipitation, and solves the problem that the existing unsaturated Fe-N site further aggravates the precipitation of the Fe site due to the Fenton effect, and the activity is sharply reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ORR catalysts, and in particular to a dual-site FeN6-CoN4 electrocatalyst and a preparation method and application thereof. Background Art

[0002] Oxygen reduction reaction (ORR) is a key cathode reaction process in new energy storage and conversion devices, such as zero-carbon emission, green and clean hydrogen fuel cells / proton exchange membrane fuel cells, zinc-air batteries, etc. However, its sluggish reaction kinetics of 4 electrons requires scarce and expensive precious metal Pt-based catalysts to be effectively driven, and the cost is high (accounting for about 40% of the electric propulsion cost). Therefore, the invention of low-cost, high-performance non-precious metal ORR catalysts is conducive to accelerating the commercialization of green energy devices such as hydrogen fuel cells and zinc-air batteries.

[0003] At present, transition metal nitrogen carbon (MNC) catalysts are considered to be the most active ORR catalysts, especially single-atom Fe-NC electrocatalysts, which are recognized as effective substitutes for precious metal platinum (Pt)-based catalysts. However, the existing technology usually involves high-temperature carbonization of metal organic framework materials containing Fe / -CO, or pyrolysis of porous carbon materials after adsorption of Fe / -CO metal sources, acid etching to remove metal particles, and obtaining single-site Fe-Nx / Co-Nx (x=1-4), which is also rarely reported, or double-site Fe-Nx-Co-Nx (x=1-4) catalysts. However, in the 4-electron oxygen reduction process, a small amount of two-electron ORR process cannot be avoided, resulting in continuous enrichment of hydrogen peroxide (H2O2) and its intermediates in the cathode catalyst layer. Due to the unsaturated characteristics of Fe-Nx, the Fe-H2O2 Fenton reaction is further aggravated, promoting the precipitation of active Fe sites, accelerating the decomposition of FeNx active sites, and sharply reducing the ORR activity and stability.

[0004] At present, transition metal nitrogen carbon (MNC) catalysts are considered to be the most active ORR catalysts, especially single-atom Fe-NC electrocatalysts, which are recognized as effective substitutes for precious metal platinum (Pt)-based catalysts. However, the existing technology usually involves high-temperature carbonization of metal organic framework materials containing Fe / -CO, or pyrolysis of porous carbon materials that adsorb Fe / -CO metal sources, acid etching to remove metal particles, and obtaining single-site Fe-Nx / Co-Nx (x=1-4), which is rarely reported, or dual-site Fe-Nx-Co-Nx (x=1-4) catalysts. However, the 4-electron oxygen reduction process is also accompanied by a certain 2-electron reduction to hydrogen peroxide (H2O2). Due to the unsaturated characteristics of Fe-Nx, the Fe-H2O2 Fenton reaction is further aggravated, promoting the precipitation of active Fe sites, and sharply reducing the ORR activity and stability. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a dual-site FeN6-CoN4 electrocatalyst and a preparation method and application thereof in view of the deficiencies in the prior art.

[0006] The technical solution of the present invention is as follows:

[0007] A method for preparing a dual-site FeN6-CoN4 electrocatalyst comprises the following steps:

[0008] Step 1: Synthesize carbon nitride C3N4;

[0009] Step 2: Take the C3N4 carrier and evenly disperse it in deionized water by ultrasonic and stir, add pyrrole monomer dropwise, keep it for 18-24 hours, use electrostatic interaction to adsorb the monomer, add Co salt and Fe salt in a molar ratio of 3:1-3:3, continue stirring for 18-24 hours, then filter, vacuum dry at 80°C for 8-12 hours, anneal at 200°C and 900°C in a nitrogen atmosphere in a tubular furnace for 2 hours each, cool to room temperature, etch with 0.5M H2SO4 solution at 80°C for 8-12 hours, wash by centrifugation until neutral, and vacuum dry at 60°C for 8-12 hours to obtain the target catalyst FeN6-CoN4.

[0010] The preparation method comprises the following steps: taking 20-30 g of urea, thiourea or melamine and spreading them evenly in a crucible and placing them in a muffle furnace for roasting for 3-5 hours, and taking out the sample after cooling to obtain C3N4.

[0011] In the preparation method, in the first step: the calcination temperature is 500°C and the heating rate is 5°C / min.

[0012] In the preparation method, in the second step, the C3N4 carrier is ultrasonically evenly dispersed in deionized water at a ratio of 1:250 (g / ml).

[0013] In the preparation method, in the second step, the amount of pyrrole monomer used is 1.5-2 ml of pyrrole monomer added dropwise to every 1 g of C3N4.

[0014] A dual-site FeN6-CoN4 electrocatalyst prepared according to any of the preparation methods described.

[0015] Application of the dual-site FeN6-CoN4 electrocatalyst in oxygen reduction reaction (ORR).

[0016] The present invention proposes a FeN6-CoN4 dual-site electrocatalyst with the highest Fe coordination; the CoN4 site not only serves as an oxygen reduction active site, but also the dual-site synergistic effect enhances the oxygen reduction catalytic activity, promotes the oxygen adsorption cracking mechanism (*O2→2*O), reduces the combined mechanism (*O2+H2O+e-→*OOH+OH-), reduces H2O2, and at the same time the saturated coordination structure FeN6 enhances the stability of the Fe site and inhibits Fe precipitation, thus solving the problem that the existing unsaturated Fe-N site further aggravates the precipitation of the Fe site due to the Fenton effect, resulting in poor stability and a sharp decrease in activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 X-ray diffraction pattern (XRD);

[0018] Figure 2 .(a) Transmission electron microscopy (TEM) image of the catalyst: (b) spherical aberration corrected transmission electron microscopy; (c, d) energy spectrum distribution diagrams of the elements Fe and Co respectively; (e, f) synchrotron radiation R spatial resolution;

[0019] Figure 3 .(a, b) Transmission electron microscopy (TEM) images of the catalyst: (c) Spherical aberration corrected transmission electron microscopy;

[0020] Figure 4 .(a, b) Transmission electron microscopy (TEM) images of the catalyst: (c) Spherical aberration corrected transmission electron microscopy;

[0021] Figure 5 .(a, b, c) Transmission electron microscopy (TEM) images of the catalyst: (d) Spherical aberration corrected transmission electron microscopy;

[0022] Figure 6 .0.1M oxygen saturated KOH aqueous solution as electrolyte, LSV of Pt / C before and after aging for 10k cycles.

[0023] Figure 7 .Implementation case 1: 0.1M oxygen saturated KOH aqueous solution as electrolyte, LSV before and after aging for 10k cycles.

[0024] Figure 8 .Implementation case 2: 0.1M oxygen saturated KOH aqueous solution as electrolyte, LSV before and after aging for 10k cycles

[0025] Fig. 9 .Implementation case 3: 0.1M oxygen saturated KOH aqueous solution as electrolyte, LSV before and after aging for 10k cycles.

[0026] Fig.10 Comparison 1: 0.1M oxygen saturated KOH aqueous solution as electrolyte, LSV before and after aging for 10k cycles

[0027] Fig.11 .(a,b) Zinc-air battery IT test and specific energy and specific capacity curves; (c,d) Open circuit voltage and LED display of zinc-air battery with FeN6-CoN4 as working electrode.

[0028] Fig.12 Analysis of element states on the catalyst surface of implementation case 1 and comparative case 1. (a, b) High-resolution N1s spectra; (c, d) Enlarged UV photoelectron spectra. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with specific embodiments.

[0030] Implementation Case 1:

[0031] Step 1: Synthesis of carbon nitride (C3N4)

[0032] Take 20-30 grams of urea and spread it evenly in a crucible. Put it into a muffle furnace and roast it at 500℃ for 3-5h with a heating rate of 5℃ / min. After cooling, take out the sample to obtain C3N4.

[0033] Step 2: Take 1.0g of the above C3N4 carrier and ultrasonically disperse it uniformly in 250mL deionized water and stir it for 1h, then add 1.5mL of pyrrole monomer and keep it for 18-24h, use electrostatic interaction to adsorb the monomer, add 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O and continue stirring for 18-24h. During this process, the metal ions are adsorbed and polymerized by in-situ pyrrole monomer to form a Fe-Co-N precursor complex; then filter, vacuum dry at 80℃ for 8-12h, anneal at 200℃ and 900℃ in a nitrogen atmosphere in a tubular furnace for 2h each, cool to room temperature, etch with 0.5M H2SO4 solution at 80℃ for 8-12h, centrifuge and wash until neutral, and vacuum dry at 60℃ for 8-12h to obtain the target catalyst FeN6-CoN4.

[0034] It is worth noting that since the metal salt is added to the aqueous solution, the effect of using a metal salt without crystal water is the same, and it will not be expanded here as an implementation plan. The inductively coupled plasma (ICP) test content is 0.84wt Fe %、1.05wt Co %.

[0035] XRD( Figure 1 ) There are no characteristic diffraction peaks of metal Fe, Co and their complexes, only the diffraction peak of Ca.25° is attributed to the (001) crystal plane of graphitized carbon, suggesting that the modified experimental method can be used to prepare single-atom dispersed site transition metal-based catalysts.

[0036] Figure (2a) shows that the catalyst is a flaky porous structure, which is conducive to promoting the mass transfer of intermediate species (*O2, *OH, *O, *OOH, etc.) in the oxygen reduction reaction and accelerating the reaction process. No metal particles were observed, suggesting the single-atom dispersion state of iron (Fe) and cobalt (Co). The large number of "bright spots" in Figure (2b) confirm the single-atom metal sites. Figure 2 c-2d shows the distribution of Fe and Co. In addition, synchrotron radiation spectroscopy ( Figure 2 e-2f) The precise structure of the catalyst is analyzed to be FeN6-CoN4, which is the first time that a dual-site highest-coordination Fe-based ORR catalyst has been synthesized.

[0037] Implementation Case 2: Same as Implementation Case 1, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O were replaced by 15mmol CoCl2·6H2O and 5mmolFeCl3·6H2O. The inductively coupled plasma (ICP) test showed that the content was 2.09wt% Fe %、0.37wt Co %.

[0038] Figure (3a) shows that the catalyst has a lamellar porous structure, which is conducive to promoting the mass transfer of intermediate species (*O2, *OH, *O, *OOH, etc.) in the oxygen reduction reaction and accelerating the reaction process. No metal particles were observed, suggesting the single-atom dispersion state of iron (Fe) and cobalt (Co). A large number of "bright spots" in Figure (3c) verify the single-atom metal site. Since the metal ions form a Fe-Co-N precursor complex through in-situ adsorption and polymerization of pyrrole monomers, the Fe-Co bimetallic site catalyst was also successfully prepared in Example 2.

[0039] Implementation case 3: Same as implementation case 1, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O were replaced by 5mmol CoCl2·6H2O and 15mmolFeCl3·6H2O. The inductively coupled plasma (ICP) test showed that the content was 2.35wt% Fe %、0.05wt Co %.

[0040] Figure (4a) shows that the catalyst is a lamellar porous structure (some "black balls" are obtained by excessive Fe3+ oxidation polymerization of pyrrole monomers), which is conducive to promoting the mass transfer of intermediate species (*O2, *OH, *O, *OOH, etc.) in the oxygen reduction reaction and accelerating the reaction process. No metal particles were observed, suggesting the single-atom dispersion state of iron (Fe) and cobalt (Co). A large number of "bright spots" in Figure (4c) verify the single-atom metal sites. Since the metal ions are adsorbed in situ and polymerized into pyrrole monomers to form Fe-Co-N precursor complexes, the Fe-Co dual-metal site catalyst was also successfully prepared in Implementation Case 3.

[0041] Comparative case 1: Same as implementation case 1, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O were replaced with 20mmolFeCl3·6H2O to make a pure Fe-N catalyst to verify the influence of Co-N site on the catalytic performance of Fe-N site. The inductively coupled plasma (ICP) test content was 3.85wt Fe %.

[0042] Figures (5a-5b) show that the catalyst is a spherical carbon support structure, which is obtained by oxidative polymerization of the pyrrole monomer adsorbed by C3N4 by excessive Fe3+ stripping. C3N4 is decomposed during the high-temperature carbonization process, and no metal particles are observed, suggesting the single-atom dispersion state of iron (Fe). The large number of "bright spots" in Figure (5d) verify the single-atom Fe metal site, so the Fe metal site catalyst was successfully prepared by comparison with Case 1.

[0043] Comparative Example 2: Same as Example 1, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O were replaced with 20mmolCoCl2·6H2O to make a pure Co-N catalyst to verify the activity of the Co-N site alone. However, the divalent Co2+ alone was not sufficient to oxidize the polymerized pyrrole monomer, so no Co-N precursor complex was obtained after the experiment.

[0044] Comparative Case 3: Same as Implementation Case 1, except that the annealing temperature in “annealing at 200°C and 900°C for 2h each in a tubular furnace in a nitrogen atmosphere and cooling to room temperature” was changed to “annealing at 200°C and 700°C for 2h each in a nitrogen atmosphere”. Due to the low calcination temperature, the dual active sites of Fe-N and Co-N cannot be fully carbonized to form, resulting in poor activity.

[0045] Comparative Case 4: Same as Implementation Case 1, except that the annealing temperature in “annealing at 200°C and 900°C for 2h each in a tubular furnace in a nitrogen atmosphere and then cooling to room temperature” is changed to “annealing at 200°C and 1050°C for 2h each in a nitrogen atmosphere”. Due to the high calcination temperature, excessive agglomeration of metal ions will aggravate the decomposition of the catalytic carbon layer, while excessive loss of nitrogen will lead to low density of Fe-N and Co-N dual active sites, and collapsed pore structure will block mass transfer, resulting in poor activity.

[0046] Alternative 1:

[0047] Step 1: Synthesis of carbon nitride (C3N4)

[0048] Take 20-30 grams of thiourea crucible and place it in a muffle furnace and calcine at 500℃ for 3-5h with a heating rate of 5℃ / min. After cooling, take out the sample to obtain C3N4.

[0049] Step 2: Same as step 2 of implementation case 1.

[0050] Alternative 2:

[0051] Step 1: Synthesis of carbon nitride (C3N4)

[0052] Take 20-30 grams of melamine crucible and put it into a muffle furnace and calcine it at 500℃ for 3-5h with a heating rate of 5℃ / min. After cooling, take out the sample to obtain C3N4.

[0053] Step 2: Same as Step 2 of Implementation Case 1

[0054] Alternative 3:

[0055] Step 1: Synthesis of carbon nitride (C3N4)

[0056] Take 20-30 grams of dicyandiamide in a crucible and place it in a muffle furnace and calcine at 500℃ for 3-5h with a heating rate of 5℃ / min. After cooling, take out the sample to obtain C3N4.

[0057] Step 2: Same as Step 2 of Implementation Case 1

[0058] Alternative solution 4: Same as alternative solution 1, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O are replaced by 10mmol Co(NO3)2·6H2O and 10mmol Fe(NO3)3·6H2O. It is worth noting that since the metal salt is added to the aqueous solution, the effect of using a metal salt without crystal water is the same, and it will not be discussed here as an alternative solution.

[0059] Alternative 5: Same as Alternative 2, except that 10.0mmol CoCl2·6H2O and 10mmolFeCl3·6H2O are replaced by 10mmol Co(NO3)2·6H2O and 10mmol FeCl3·6H2O or 10.0mmol CoCl2·6H2O and 10mmol Fe(NO3)3·6H2O.

[0060] Catalyst performance characterization:

[0061] A 0.1 M oxygen-saturated KOH aqueous solution was used as the electrolyte, and a carbon rod and a rotating disk electrode (RDE, with an effective area of ​​0.19625 cm -2 )Hg / HgO were counter electrode, working electrode and reference electrode respectively. The electrochemical workstation was CHI760E. The catalytic activity was tested by linear sweep polarization curve (LSV). The benchmark precious metal catalyst Pt / C was purchased from Johnson Matthey (Shanghai) Chemical Co., Ltd.

[0062] like Figure 6 As shown, the Pt / C half-wave potential (E 1 / 2 ) is 0.842V, and after 10,000 cycles (10K) of cyclic voltammetry (CV) accelerated aging (ADT), the half-wave potential will be reduced to 0.794V, attenuating by 48mV.

[0063] like Figure 7 As shown, the half-wave potential (E 1 / 2 ) is as high as 0.886V, which is 44mV higher than Pt / C. After 10,000 cycles (10K) of cyclic voltammetry (CV) accelerated aging (ADT), the half-wave potential remains at 0.879V, with only a decay of 7mV, showing very excellent ORR catalytic activity and stability.

[0064] like Figure 8 As shown in Example 2, Fe-Co catalyst half-wave potential (E 1 / 2 ) is 0.864V, close to Pt / C 0.842V, but after 10,000 cycles (10K) of cyclic voltammetry (CV) accelerated aging (ADT), the half-wave potential remains at 0.821V, attenuated by 24mV, and the catalytic stability is significantly better than that of the benchmark catalyst Pt / C.

[0065] like Fig. 9 As shown in Example 3, Fe-Co catalyst half-wave potential (E 1 / 2 ) is 0.845V, which is 22mV higher than Pt / C. After 10,000 cycles (10K) of cyclic voltammetry (CV) accelerated aging (ADT), the half-wave potential remains at 0.849V, attenuated by 15mV, showing very excellent ORR catalytic activity and stability, which is significantly better than the benchmark catalyst Pt / C.

[0066] like Fig.10 As shown in Example 3, Fe-Co catalyst half-wave potential (E 1 / 2 ) is 0.837V, slightly lower than Pt / C. After 10,000 cycles (10K) of cyclic voltammetry (CV) accelerated aging (ADT), the half-wave potential remains at 0.801V, attenuated by 36mV, but still has a certain stability.

[0067] Battery performance test:

[0068] like Fig.11 (a, b), zinc-air battery assembled with catalyst FeN6-CoN4 ( Fig.11 a) Discharge for more than 9000s at an industrial-grade current of 500mAcm-2 and a voltage of about 0.9V (the output voltage of Pt / C continues to decrease, and water flooding / oxygen starvation occurs at about 8000s, the ORR oxygen reduction reaction turns into hydrogen evolution (HER), the potential reverses, and the reaction stops), with a specific energy of 988Wh Kg Zn-1 (91% of theoretical value) and a specific capacity of 778mAh gZn-1 (95% of theoretical value), which is far superior to the benchmark precious metal Pt / C catalyst; Fig.11 (c, d) Demonstrations include an open circuit voltage of up to 1.65V (theoretical value 1.68V) and excellent LED performance (“Zn-air” and “1@PDSU” continuously light up for more than 36 hours).

[0069] Catalyst performance analysis:

[0070] From the examples 1-3 and the comparative examples, the ORR catalytic activity and stability decrease with the decrease of Co site content, although the comparative example 1 has the highest metal site content of 3.85 Wt Fe %, significantly higher than 1.89Wt in case 1 Fe+Co % (0.84wtFe%, 1.05wtCo%). This is mainly because the similar content of heteronuclear Fe\Co sites promotes charge transfer, enhances metal-support interaction, optimizes the adsorption / desorption of oxygen-containing intermediate species, and improves the intrinsic activity of the catalytic site. In addition, the synergistic effect of the Co site enhances the oxygen reduction catalytic activity, promotes the oxygen adsorption and cracking mechanism (*O2→2*O), reduces the joint mechanism (*O2+H2O+e-→*OOH+OH-), reduces H2O2, and at the same time, the saturated coordination structure FeN6 enhances the stability of the Fe site and inhibits Fe precipitation, solving the problem that the existing unsaturated Fe-N site is further aggravated by the Fenton effect. The precipitation of the Fe site is poor, and the activity is sharply reduced.

[0071] In addition, the N element state of the catalysts in Example 1 and Comparative Example 1 was analyzed by X-ray photoelectron spectroscopy (XPS). High-resolution N1s ( Fig.12 a) The spectra at 398.2, 400.4, 402.3, and 404.2 eV can be fitted to pyrrolic N, pyridinic N, graphitic N, and N oxide, respectively. The binding energies of pyridinic N and pyrrolic N in the comparative case are negatively shifted by 0.3 and 0.5 eV. XPS results verify that the M (Fe-Co) double site in implementation case 1 promotes electron transfer to the N element, which is consistent with the Bader charge results obtained by first-principles calculations (Comparative case 1: Fe loses 1.12 e-; implementation case: Fe+CO=0.83+1.04=1.92e- - ), enhancing the MN interaction, optimizing the adsorption-desorption behavior of oxygen-containing intermediate species, accelerating the ORR kinetics, and improving the intrinsic activity. In addition, ultraviolet photoelectron spectroscopy (UPS) was used to further explore the electronic structure and charge transfer properties of the catalyst surface. Fig.12 c shows the secondary electron cutoff edge (E cutoff ) is 16.76 eV, according to equation E Ф =21.22eV-E cutoff The calculated work function is 4.46, which is smaller than 4.64 in comparative case 1, revealing the enhanced electron transfer, which makes it easier to provide electrons to oxygen-containing intermediate species and promotes reaction kinetics. At the same time, the valence band maximum (VBM) position of implementation case 1 is 2.41 eV, which is closer to the Fermi level, i.e., the d electron energy (E d ) increases, the degree of electron delocalization increases, and Fig.12 The a-12b and Bader charge results are consistent.

[0072] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

Claims

1. A method for preparing a dual-site FeN6-CoN4 electrocatalyst, characterized in that: The following steps are involved: Step 1: Synthesize carbon nitride C3N4; Step 2: Take the C3N4 carrier and evenly disperse it in deionized water by ultrasonic and stir, add pyrrole monomer dropwise, keep it for 18-24 hours, use electrostatic interaction to adsorb the monomer, add Co salt and Fe salt in a molar ratio of 3:1-3:3, continue stirring for 18-24 hours, then filter, vacuum dry at 80°C for 8-12 hours, anneal at 200°C and 900°C in a nitrogen atmosphere in a tubular furnace for 2 hours each, cool to room temperature, etch with 0.5 M H2SO4 solution at 80°C for 8-12 hours, wash by centrifugation until neutral, and vacuum dry at 60°C for 8-12 hours to obtain the target catalyst FeN6-CoN4.

2. The preparation method according to claim 1, characterized in that: The first step is: take 20-30 grams of urea, or thiourea, or melamine and spread it evenly in a crucible and put it in a muffle furnace for roasting for 3-5 hours. After cooling, take out the sample to obtain C3N4.

3. The preparation method according to claim 2, characterized in that: In the first step: the calcination temperature is 500°C and the heating rate is 5°C / min.

4. The preparation method according to claim 1, characterized in that: In the second step, the C3N4 carrier is ultrasonically uniformly dispersed in deionized water at a ratio of 1:250 g / ml.

5. The preparation method according to claim 1, characterized in that: In the second step, the amount of pyrrole monomer used is 1.5-2 ml of pyrrole monomer added dropwise to every 1 g of C3N4.

6. A dual-site FeN6-CoN4 electrocatalyst prepared according to any one of the preparation methods described in claims 1-5.

7. Application of the dual-site FeN6-CoN4 electrocatalyst according to claim 6 in oxygen reduction reaction (ORR).

Citation Information

Patent Citations

  • Gram-level high-oxidation-state monatomic site FeN5 electrocatalyst as well as preparation method and application thereof

    CN114852974A

  • KR20230127767A